O ensinar e aprender de professores da Educação Tecnológica no IFMT Campus Cuiabá – Octayde Jorge da Silva - Silva, Amarilia Mathilde da (2011)
This research aims to understand how is the process of teaching technical subjects in the area for the course of Technology in System Development for Internet and for the course of Computer Network Technology from IFMT - Campus Cuiabá Octayde Jorge da Silva. Many teachers, belonging to the former teaching staff of 1st and 2nd degrees, minister, currently teaching graduate courses in technology. Guided by theorists like Bogdan and Biklen (1994), Lüdke and André (1986), Cunha (2009), Bauer (2004), Souza (2008) and others, this qualitative research was accomplished through analysis of documents, written narratives, classroom observations, development of protocols of observations and narrative interviews. During the research, were used as reference some theorists who argue about teacher training, knowledge of teaching and learning, as Nóvoa (1995), García (1999), Imbernón (2010), Shulman (1986, 2004), Mizukami (2002), Huberman (2000), Pérez Gómez (1992), Roldão (2010), Sacristan (1995), Zeichner (1992) and others. Analyses of data reveal that teachers surveyed in this study are at different stages of teaching, taking as reference the set of personal and professional experiences built along their training path and how their experiences are marked by scientific research on the route master, doctoral and postdoctoral studies, some teachers rely predominantly on research as a source of content for the student to build specific content knowledge so that the surveyed theories can being applied in practical activities. Also proved to be a teacher in technology education involves, for teachers, the constant search for the update in order to follow the dynamic and complex technological environment. However, it is evident in reports that there is a sense of isolation in the pursuit of this update, since the institution, the locus of this research does not provide conditions so that, they can develop professionally in a shared form.